The Effect of Exercises Using Equipment on Learning the Skill of Half-Turn Landing Inward on the Pommel Horse for Students - Mohsen, Ali (Journal of Physical Education, 2025)
Artistic gymnastics is one of the individual sports, and it is considered one of the most difficult due to its significant physical and motor requirements. Additionally, it involves numerous apparatuses, each containing multiple skills that students must learn. This study aimed to investigate the effect of exercises using equipment on learning the skill of half-turn inward landing on the pommel horse. The research hypothesis proposed that there are statistically significant differences between the post-test results of the control and experimental groups in learning the half-turn inward landing skill on the pommel horse, in favor of the experimental group.The researcher used the experimental method, which is suitable for the nature of the study. The study population comprised 340 students distributed across 10 sections of the second year at the College of Physical Education and Sports Sciences, University of Baghdad. The sample for the study was drawn from second-year students in Section (H), with a total of 28 students. After excluding those injured or failed, the final sample consisted of 20 students, representing 5.88% of the total population. The researcher employed a design with two equivalent groups: a control group and an experimental group, as this design suited the research procedures.Conclusions: Based on the results, the researcher concluded the following: The exercises designed using the correct scientific approach play a significant role in helping students and instructors learn the skill faster. The equipment used provided real support for the technical pathways of performance, facilitating the learning of the half-turn inward landing skill on the pommel horse. The researcher recommends the continued use of these exercises and equipment to teach this skill to students.